Peran Tesla Dalam Transisi Mobil Listrik dan Energi Bersih: Analisis Ekologi Politik - Rachmandio Nadhl Jaenudin; Raden Maisa Yudono (Jurnal Sentris, 2025)
Clean energy has become one of the central issues in International Relations as the impacts of climate crisis and environmental degradation become increasingly tangible. The urgency to move away from fossil fuel-based transportation towards electric vehicles is not merely a technological choice, but also part of political dynamics involving multiple actors with competing interests. This study aims to analyze Tesla’s role in the transition to electric vehicles and clean energy in the United States using a political ecology approach, which positions multinational corporations as actors that shape environmental governance. A qualitative instrumental case study design is employed, relying on document studies of government regulations, corporate reports, and academic literature. The findings show that Tesla functions not only as an electric vehicle manufacturer, but also as a form of political pressure contributing to the strengthening of clean energy regulations during Joe Biden’s presidency following regulatory rollbacks under Donald Trump. At the same time, the study reveals critical consequences, particularly regarding the ecological footprint of battery supply chains and the risk of environmental injustice in mineral-producing countries. Political ecology thus helps to demonstrate that the clean energy transition is deeply embedded in power relations and cannot be understood as a neutral, purely technocratic process.